2011
DOI: 10.1080/01635581.2011.589957
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Fat and Omega-3 Fatty Acids on Urinary Eicosanoids and Sex Hormone Concentrations in Postmenopausal Women: A Randomized Controlled Feeding Trial

Abstract: Substantial evidence relates increased sex hormone concentrations with increased breast cancer risk. Varying omega-3 (n-3) fatty acid (FA) intake may lead to alterations in eicosanoid balance and changes in circulating sex hormones that reduce risk. To clarify effects of dietary fat and n-3 FA intake on breast cancer risk markers, circulating sex hormones and urinary eicosanoids were measured in response to controlled feeding of diets designed to increase plasma concentrations of n-3 FA. A controlled cross-ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 35 publications
1
41
0
1
Order By: Relevance
“…In a smaller controlled, crossover feeding trial of 16 postmenopausal women, a low-fat diet and a low-fat, high v-3 diet were associated with a higher excretion of urinary estrogens (42). In the same study, no relative increase in sex hormones measured in blood was found (43). It is possible that, in overweight and obese women, increased estrogen production from adipose tissue in conjunction with that from v-3 intake may lead to a greater risk.…”
Section: Discussionmentioning
confidence: 71%
“…In a smaller controlled, crossover feeding trial of 16 postmenopausal women, a low-fat diet and a low-fat, high v-3 diet were associated with a higher excretion of urinary estrogens (42). In the same study, no relative increase in sex hormones measured in blood was found (43). It is possible that, in overweight and obese women, increased estrogen production from adipose tissue in conjunction with that from v-3 intake may lead to a greater risk.…”
Section: Discussionmentioning
confidence: 71%
“…However, studies of nonsteroidal anti-inflammatory drugs suggested an inverse association in obese women only (47). There is limited evidence that v-3 is associated with endogenous sex hormones (48), but findings from a number of small controlled feeding trials were inconsistent (49)(50)(51)(52)(53). That the association between LCv-3PUFA and endometrial cancer was restricted further to type I cancers, which are considered estrogen-responsive (54), strongly suggested interrelations in fatty acids, sex hormones, inflammation, and cancer risk.…”
Section: Discussionmentioning
confidence: 98%
“…EPA + DHA:EPA and DHA are long chain n-3 fatty acids that are precursors of hormones known as eicosanoids which play important roles in biological processes within the body. [26] According to American Heart Association about 1.0 g/day of EPA+DHA, or two servings of fatty fish per week reduce the risk of death from coronary heart disease. [27] Consequently, "EPA (2014) In another study have shown in cooked kutum roach (Rutilus frisii kutum) the "EPA+DHA" content reduced during cooking procedure which supports our findings about reduction of "EPA+DHA" content.…”
Section: Proximate Compositionmentioning
confidence: 99%